Study on acrylamide accumulation in the model system based on animal raw materials depending on thermal treatment regimes - A. S. Dydykin; O. K. Derevitskaya; A. N. Ivankin; A. V. Kulikovskii; E. I. Dragunskaya (Пищевые системы)
The aim of the investigation was to study an effect of thermal treatment parameters on the content of reducing sugars, amino acids and acrylamide in the meat model system depending on the thermal treatment regime. The authors studied an influence of the reaction of melanoidine formation on the concentration of amino acids and reducing sugars at different thermal treatment regimes and established a decrease in the total amino acid content by 7 % upon the standard sterilization regime and by 11 % when increasing the temperature or duration of thermal treatment. It was found that at the same temperature with an increase in duration of thermal treatment up to 50 min., the acrylamide level increased by 1.6 times. Exposure of the model samples to a temperature of 120 °С for 50 min. had the highest effect on the level of acrylamide accumulation compared to the traditional sterilization regime of canned foods for child nutrition and the regime with an increased temperature of up to 130 °С. The obtained data will allow developing new meat products with the reduced content of unsafe components for nutrition in early childhood.